Konsep Manajemen Talenta dan Pengaruhnya Terhadap Kinerja Karyawan - Anisah Anisah; Sakinah AS (Universitas Batanghari, 2020)
This study aims to examine the concept of talent management and to analyze the influence of talent management, competence on employee performance. The sample in this study is employees of marketing in the banking sector in the city of Jambi. The data collection method is using a questionnaire and analyzed using verification analysis, the analysis tool in this study is using Component Based SEM (Structural Equation Modeling), namely PLS (Partial Least Square). The results of this study will explain how the influence of the main variables studied, namely talent management, competence and employee performance.